2014
DOI: 10.1080/02786826.2014.896989
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Induced Charge on Deposition of Uniformly Charged Particles in a Pediatric Oral-Extrathoracic Airway

Abstract: An in vitro study was conducted in the Alberta idealized child mouth-throat, which mimics average deposition in a set of nine 6-14-year-old subjects, to examine the enhancement of deposition of monodisperse uniformly charged particles as a result of induced electrostatic forces. A purpose-based atomizer was designed and built for generating monodisperse, uniformly charged particles. The atomizer generates droplets by jet break up under the action of capillary waves and charges them via electrostatic induction.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 43 publications
1
8
0
Order By: Relevance
“…1,2 There are a number of mathematical models and computational tools developed to understand particle flow and to predict deposition patterns of particles in the whole lung or its specific region. [3][4][5][6][7][8][9] In silico study results using these modeling tools agreed with in vitro study results as well. 10,11 In the field of aerosol medicine, there have been several methods invented and marketed to improve pharmacokinetic efficacy and effectiveness in respiratory drug delivery, and to minimize losses in the delivery devices.…”
supporting
confidence: 75%
“…1,2 There are a number of mathematical models and computational tools developed to understand particle flow and to predict deposition patterns of particles in the whole lung or its specific region. [3][4][5][6][7][8][9] In silico study results using these modeling tools agreed with in vitro study results as well. 10,11 In the field of aerosol medicine, there have been several methods invented and marketed to improve pharmacokinetic efficacy and effectiveness in respiratory drug delivery, and to minimize losses in the delivery devices.…”
supporting
confidence: 75%
“…Modifications included altering the vibration amplitude to reduce liquid output, thereby enabling evaporation to near submicrometer size at the low flow rates required for infant ventilation, and including an electrode positioned below the mesh to charge the aerosol by induction charging. Other studies have used induction charging with single orifice plates (Azhdarzadeh et al, 2014a; Azhdarzadeh et al, 2014b), but the application of induction charging to a vibrating mesh system with low airflow is a new advancement. Further details in device development and experimental testing methods for these new systems are described in the following sections.…”
Section: Methodsmentioning
confidence: 99%
“…The use of corona needles for electrospray discharge (Ijsebaert et al, 2001) is associated with ozone formation (Hinds 1999), making them impractical for use in inhalers. Vibrating orifice charged particle generators are limited by very low mass output (Azhdarzadeh et al, 2014a; Azhdarzadeh et al, 2014b; Reischl et al, 1977). …”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated the effect of charge on the deposition of micrometer (14, 1820, 23, 26) and submicrometer particles (13, 16, 25) in human airways and on boundary surfaces (2730). The study of Melandri et al (13) reported the deposition of charged monodisperse aerosols with diameters of 1 μm or less in the airways of human subjects breathing normally.…”
Section: Introductionmentioning
confidence: 99%
“…proposed a method for generating charged monodisperse particles by modifying a vibrating single orifice aerosol generator using an induction charging cap (34). This method has been used to study the penetration of monodisperse charged droplets, with a minimum size of 1 μm, through tubes of different lengths and diameters at various velocities (28), and the penetration of droplets with diameter sizes of 3–6 μm through the idealized extrathoracic airways of adults (19), children (20) and infants (23). However, a disadvantage of the single vibrating orifice system is typically low aerosol concentration (10 3 part/cm 3 ) and mass output, which may prolong or prevent the administration of pharmaceutical aerosols.…”
Section: Introductionmentioning
confidence: 99%